Analisis User Experience Dan Redesign User Interface Aplikasi Trading Elit Mobile Menggunakan Metode User Centered Design Dan System Usability Scale - Farhan Akmal Muhammad (2024)
The very rapid economic growth in Indonesia has encouraged innovation in the field of financial technology, including in stock investment. PT Erdikha Elit Sekuritas is one of the securities companies that has launched an online trading application to make it easier for investors to carry out stock transactions and monitor capital market movements via a smartphone called ELIT Mobile. However, using this application faces several challenges, including a less than optimal interface and less efficient features. To improve user experience, this research uses a User-Centered Design approach and the User Centered Design (UCD) method and System Usability Scale (SUS) to provide recommendations for design improvements that are more attractive and make it easier to use the ELIT Mobile application. This research is expected to help PT Erdikha Elit Sekuritas compete with its competitors and maintain application user satisfaction in the Indonesian market.